Outpatient Liaison Palliative Care for Children: Two Years' Experience of Non-profit Charitable Organization - Nataliya V. Minaeva; Rezeda I. Islamova; Mariya I. Bazhenova (Вопросы современной педиатрии)
The system of palliative medical care for children in Russia has been actively developing in recent years. It is important to discuss the principles of outpatient palliative care organization in different regions of the country. The experience of creation and operating of outpatient liaison pediatric service based on non-profit charitable foundation is described.